Corrosion behaviour of low-alloy martensite steel exposed to vapour-saturated CO2 and CO2-saturated brine conditions. (20th September 2016) - Liu, Zhenguang; Gao, Xiuhua; Li, Jianping; Du, Linxiu; Yu, Chi; Li, Ping; Bai, Xiaolei
Abstract: This work utilizes immersion experiments to investigate the CO2 corrosion behaviour of low-alloy martensite steel by analysing its microstructure, corrosion kinetics, corrosion phases, surface morphology, cross-section morphology and elemental distribution. The experimental results show that the designed steel is free of localized corrosion and that its corrosion rate in vapour-saturated CO2 conditions is lower than that in CO2 -saturated brine conditions. The inner layer consists of FeCO3 crystals and Cr-rich compounds, which plays a crucial role in the corrosion behaviour of the designed steel immersed in CO2 -saturated brine conditions. The corrosion processes of the low-alloy martensite steel immersed in vapour-saturated CO2 and CO2 -saturated brine conditions are proposed according to the experimental results. Additionally, the microscopic corrosion process of steel materials with a martensite microstructure is presented.